2001
DOI: 10.1152/ajpheart.2001.280.5.h2399
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic stimulation of rat resistance arteries affects Ca2+ sparks, Ca2+ waves, and Ca2+oscillations

Abstract: Confocal laser scanning microscopy and fluo 4 were used to visualize local and whole cell Ca(2+) transients within individual smooth muscle cells (SMC) of intact, pressurized rat mesenteric small arteries during activation of alpha1-adrenoceptors. A method was developed to record the Ca(2+) transients within individual SMC during the changes in arterial diameter. Three distinct types of "Ca(2+) signals" were influenced by adrenergic activation (agonist: phenylephrine). First, asynchronous Ca(2+) transients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
145
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(159 citation statements)
references
References 31 publications
13
145
1
Order By: Relevance
“…A water objective was used to obtain adequate working distance, as described previously (24). "Radial" confocal sections were used to image SMCs in cross section during active contractions (23). Individual SMCs can be successfully "tracked" during vasomotion by using radial sections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A water objective was used to obtain adequate working distance, as described previously (24). "Radial" confocal sections were used to image SMCs in cross section during active contractions (23). Individual SMCs can be successfully "tracked" during vasomotion by using radial sections.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that such asynchronous Ca 2ϩ waves, which arise from Ca 2ϩ released through inositol 1,4,5-trisphosphate receptors (InsP 3 R), are highly efficient in delivering Ca 2ϩ to MLCK that is tethered to the contractile myofilaments (20). In some small arteries, a different type of contractile Ca 2ϩ signal also may be generated, particularly when levels of receptor activation are high: Ca 2ϩ oscillations that are spatially uniform and synchronized among the different cells (6,23 ] (15, 27) but also, importantly, involves increased activity of certain protein kinases, possible transactivation of extracellular growth factor receptor, activity of the local renin-angiotensin system (RAS), and other enzymes (for review on mechanisms of MT, see Ref. 7).…”
mentioning
confidence: 99%
“…Ca 2þ oscillations induced by norepinephrine were recorded over an 11 min time-window and during this period, the Ca 2þ spike frequency and amplitude decreased spontaneously (Figure 2A), resulting from receptor desensitization as reported by others. 30,31 The Ca 2þ oscillation frequency attained 2. 51 6 0.44 spikes/min measured over the last 3 min of norepinephrine exposure (n ¼ 8, P < 0.001 compared with control without norepinephrine, in which case the frequency was zero).…”
Section: Norepinephrine Triggers Repetitive Ca 2þ Oscillations In Smcmentioning
confidence: 98%
“…In some vessels, asynchronous oscillations of individual VSMC maintain a particular vascular tonus. However, in small resistance vessels the oscillations of groups of cells are synchronized through gap-junctions resulting in the pulsative contractile response [34,45,79,80]. This oscillatory activity can be regulated by variations of neurotransmitters following sympathetic activation and can affect contractile tone through the increase of frequency, thereby increasing blood flow or tissue oxygenation [43,45,46,81].…”
Section: Calcium Cycling In Contractile Tonic and Phasic Vsmcmentioning
confidence: 99%